Perlindungan Hukum terhadap Saham yang Diperjualbelikan oleh Investor melalui Transaksi Online - Siregar, Emiel Salim; Manasar, Andrew; Sembiring, Roy Imanta; Sitindaon, Krisman; Juwanti, Tika; Barus, Tri Vena Agintha; Panjaitan, Sofyan; Adelia, Cici (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The rapid development in the capital market in today's technology has influenced transactions in the capital market for buying and selling directly using online media. The intermediary system provided by securities trading on electronic media, namely the internet, in an application developed in the digital era at present, allows access and trading of stocks directly using electronic devices like smartphones. This research uses normative law research, which examines written laws from various aspects such as theory, history, philosophy, comparison, structure, composition, scope, material, and consistency of general explanations and articles, formality and binding force of a law, language used, as well as institutions and legal subjects.